Pengaruh Penambahan Lempung Terhadap Kuat Geser dan Kerapatan Pasir - Desmarita Tarjudin; Nurly Gofar (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2022)
In soil mechanics, soil is generally categorized as sand and clay. The term sand represents a cohesionless coarse-grained while clay is a fine-grained soil with shear strength mainly derived from cohesion. In loose conditions the sand has low shear strength and is prone to shear failure. Many studies have been carried out to study the strength properties of sand and clay mixtures. In this case, the effect of clay content on the angle of repose is studied and also on the shear strength of the sand tested through direct shear testing. In addition, sand density testing was performed to identify the mechanism of shear strength increase when the sand is mixed with clay. That the angle of repose of the sand used in this study was 30o. The angle increased liniearly with the addition of clay because the clay which has finer grain characteristics can fill the void of sand resulting in a more stable mound with steeper angle. From the direct shear test results, it was found that the addition of clay resulted in an increase in the internal shear angle. The soil cohesion increases with the addition of clay up to 20% and then decreases. The same results were obtained from the results of the soil density test where the maximum sand density was obtained at the clay content of 20%-25%.